BAM8-22 targets spinal MrgC receptors to modulate UPRmt activity in the mechanism of bone cancer pain - Xie, Mingming; Li, Dan; Zeng, Haohao; Huang, Yulin; Xu, Rui; Wang, Zhen; Yu, Jiacheng; Sun, Yu’e (Frontiers in Pharmacology, 2025)
BackgroundBone cancer pain (BCP) significantly impacts patients’ overall quality of life. Cellular energy metabolism homeostasis is critically dependent on mitochondrial integrity, and emerging evidence suggests that mitochondrial dysfunction in chronic BCP exacerbates pain progression by disrupting nociceptive signaling pathways. Notably, G protein-coupled receptors (GPCRs), a major class of membrane receptors, modulate mitochondrial function through diverse molecular mechanisms. In this study, we investigated the role of Mas-related G protein-coupled receptor C (MrgC) in BCP pathogenesis and its regulatory effects on mitochondrial function.MethodsMale C3H/HeN mice were utilized to establish a BCP model. Transmission electron microscopy and flow cytometry were employed to assess changes in mitochondrial ultrastructure, as well as levels of mtROS, ATP, and MMP in mice experiencing BCP. Following intrathecal injection of BAM8-22, we analyzed the effects of activated MrgC on mitochondrial unfolded protein response (UPRmt)-related molecules (ATF5, HSP60, LONP1, CLPP) and pain-related behaviors in BCP mice. The regulatory mechanism of MrgC on UPRmt was further explored in N2a and 293T cells.ResultsMice with bone cancer pain showed improved mRNA and protein levels of UPRmt-related molecules, increased MMP and ATP, decreased mitochondrial ROS levels in the spinal cord after receiving an intrathecal injection of BAM8-22. Additionally, the paw withdrawal mechanical threshold in BCP mice increased, while the number of spontaneous foot lifts decreased. In complementary cellular studies, transfection-mediated overexpression of MrgC in N2a cells enhanced UPRmt biomarker expression, whereas RNA interference-mediated MrgC knockdown produced the opposite effect.ConclusionBy activating spinal MrgC to mediate UPRmt activity and protect mitochondrial function, BAM8-22 contributes to the molecular development of BCP. This discovery suggests a new therapeutic target for BCP and offers a possible research avenue.